EXECUTIVE SUMMARY (Tufts Archival Research Center, 2007)
Executive summary for the week of April 24, 1987. Discusses legislation in the states as well as on the federal level. Mentions the major developments for that week which include the rejection of proposed regulations of smoking in public places as unconstitutional.